"The Theatricality of the Emulsion!": Queerness, Tactility, and Abstraction in the Hand-Processed Films of Roger Jacoby. Issue 2 (1st December 2019) - Ogrodnik, Benjamin
Abstract : This article reexamines the career of Roger Jacoby (1945–1985), an abstract painter and gay liberation activist who became renowned for processing film in his darkened bathtub and for films that featured his partner, Ondine, the Andy Warhol Superstar. Through a consideration of film shorts made in the 1970s and 1980s, the article argues that Jacoby's principal innovation was the exploration of hand-processing, which resulted in films that resembled abstract expressionist paintings in motion. Additionally, it considers hand-processing as an overlooked, albeit powerful, vehicle for expressing non-normative sexuality in American avant-garde film. It situates Jacoby alongside gay filmmakers Kenneth Anger, Gregory Markopoulos, and Jack Smith, and considers how hand-processed media can generate a "corporealized" spectator and disrupt patterns of filmic illusionism and heterosexist protocols of sexual/gender representation.